Efforts to Reduce Cargo Residue After Tank Cleaning Last Cargo Palm Stearin to Next Cargo Palm Olein in MT Loading Tank. TIRTASARI - Farrahi, Naufal Afif; Lestari, Elise Dwi; Eddi, Eddi; Widyaningsih, Upik (Journal of Engineering Science and Technology Management, 2026)
On chemical tanker ships, in addition to having strict safety regulations, the cargo is varied, sometimes with 2 or 3 different cargoes to be loaded. This requires the cargo tanks to be cleaned before loading the next cargo; however, there are often still cargo residues that can affect the quality of the cargo and cause failure during cargo tank inspections. This study aims to reduce the cargo residues that remain in the cargo tanks by observing several possible causes of the residues. This research uses descriptive qualitative research methods to address the problems occurring on the ship and employs data collection techniques including observation, interviews, and documentation, conducted while the researcher carried out sea practice on the MT Tirtasari ship for 12 months and 5 days, from October 5, 2023, to October 10, 2024.